Modeling and simulation of biomass pyrolysis and gasification processes - Maldonado, Pedro (2022)
In computer simulation, the processes and equipment operate following the sequence of input data, data processing, and return output data. Typically, these data are mass flows, temperatures, compositions, and pressures. Specifically, modeling and simulation of gasification systems aid in predicting the outlet gas composition when operating conditions and scale size alter. This assists in planning the construction or retrofitting of existing equipment. UniSim Design is a chemical process modeling software, similar to Aspen Plus and Aspen Hysys. It is used in engineering to create dynamic and steady-state models for plant design, monitoring, troubleshooting, planning, and management [1]. However, regardless of the software used for modeling and simulation of the gasification process, there is a pattern of steps that must be followed in order to successfully perform the simulation. Therefore, this process is divided into 4 main steps: Drying or removal of moisture present in the biomass until 5% w/w; followed by Pyrolysis, which was split into Devolatilization, and Char cracking, both calculated with the help of Microsoft Excel; Combustion, where oxidation equilibrium reactions are added; and finally the Reduction step, which is divided in the heterogeneous and homogeneous stages, where equilibrium reactions are also inserted